Pemanfaatan Museum Batubara Tanjung Enim Sebagai Wisata Edukasi Dan Sumber Belajar Sejarah Lokal - Maysuri, Tama; Harnisa, Susi (Program Studi Pendidikan Sejarah, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pattimura, 2025)
ABSTRACT This article aims to explore the use of the Tanjung Enim Coal Museum as an educational tourism and a source of learning about local history. The focus of the research is how this museum can be optimally utilized in education and preservation of the history of the local community. The research method used is a qualitative approach with data analysis involving observation, interviews, and literature studies related to collections and the role of museums in society. The results of the study show that the Tanjung Enim Coal Museum has great potential in improving the understanding of local history, enriching the learning experience of students, and promoting awareness of the importance of cultural preservation. The conclusion of this study is that the use of museums as educational vehicles can strengthen community ties with local history, support contextual-based education, and increase the attractiveness of sustainable educational touris. KEYWORDS Utilization, Tanjung Enim Coal Museum, Educational Tourism, Learning resources and local history.